The construction of a queer identity in Eminent Maricones - Ruz, Gerardo (2022)
Jaime Manrique’s book, Eminent Maricones (1999), is an autobiographical text that also includes the lives of other famous writers such as Manuel Puig, Reinaldo Arenas and Federico García Lorca, because they all share the queer identity to which the novel’s title refers. This text goes beyond recounting the experiences that Jaime Manrique has with these famous Hispanic writers: it also reveals the reality of the LGBTQ+ community in Latin America and the United States and how they, despite the fact of being famous, did not escape the tyrannical heteronormative society back then. At the beginning of the text, a heteronormative vision of homosexuality is presented, although the author deliberately admits to being gay. Time and maturity allowed Manrique to shed those prejudices and implant a subversive discourse; he also exposes his dual position as a Latin American and Latinx writer. All the experiences throughout his life lead Jaime Manrique to accept his sexuality and sincere love for queer people. This article analyzes this character’s coming-of-age and his queer identity. Likewise, the elements that enable him to free himself from an internalized homophobia and freely appropriate the queer subject as his true identity.